(untitled) (American International Journal of Business and Management Studies, 2020)
The Tanzanian food industry is one of the most critical sectors in the country. Small and medium enterprises (SMEs) are the largest processors of food. Although SMEs mostly deal with processing food, they still face challenges, especially with their suppliers. Though previous researchers have investigated partnership issues in SMEs, little has been reported on the factors that impact the supplier relationships found in food manufacturing SMEs. This study employed a qualitative design where semi-structured interviews with 13 experts were conducted to identify the factors that impede SRM in Dar es Salaam. The findings reveal that poor relationship management, poor storage facilities, poor transportation and inadequate production capacities are the main challenges affecting SRM within these firms. To overcome these challenges, it has been recommended to improve the supplier relationships through being transparent, fostering trust and sharing quality information with the suppliers on time. Furthermore, investment in technology has been recommended to reduce costs and to enhance the information sharing between suppliers and SMEs. Government support is required with regard to financial aid and the improvement in the infrastructure to facilitate the easier flow of goods from SMEs to the customers.